Evaluation of ICT tools accessibility to business education lecturers and students - Oluwalola Kikelomo Felicia (Journal of Education and Learning (EduLearn), 2021)
The paper evaluated the accessibility of Information and Communication Technology (ICT) tools to business education lecturers and students. Descriptive survey research design was adopted for the study. A total of 110 students and 20 lecturers were randomly selected from the department of business education for the study. Two research questions guided the study and one null hypothesis tested at 0.05 level of significance. The co-efficient of 0.86 was obtained for the research instrument. Research questions were reported as means and standard deviation values while T-test was used to test the null hypothesis. The results showed that ICT supportive tools were available for teaching and learning Business Education in Kwara State College of Education Ilorin. Hence, there was no difference in perception of lecturers and students accessibility of ICT tools. Respondents recommended provision of adequate ICT tools by the government for teaching and learning of business education. Trainings like seminars with workshop is of immense importance for ICT support staff.